Enhanching Environmental Performance (EP) through Green Organizational Culture (GOC) and Green Transformational Leadership (GTL) with Workplace Pro-Environmental Behaviour (WPEB) as Mediating Variable (Jurnal Simki Economic, 2025)
The purpose of this study is to investigate the impact of Green Organizational Culture (GOC), Green Transformational Leadership (GTL), and Workplace Pro-Environmental Behaviour (WPEB) on Environmental Performance (EP) at Batik MSMEs in Semarang. A sample of 100 respondents was selected from a population of 331 employees at 117 MSMEs, selected through purposive sampling. The research focused on MSMEs that produce batik from raw materials to finished goods. Data analysis using SPSS version 25 with a significance of 5%. The findings indicate that Environmental Performance (EP) is significantly impacted by Green Organizational Culture (GOC), Green Transformational Leadership (GTL), and Workplace Pro-Environmental Behavior (WPEB). Green Organizational Culture (GOC) and Green Transformational Leadership (GTL) also affect Workplace Pro-Environmental Behaviour (WPEB). The relationship between the two variables and Environmental Performance (EP) was found to be mediated by Workplace Pro-Environmental Behavior (WPEB). The limitation of the study lies in the scope of the population, where out of 117 MSMEs only about 15 actually function as batik producers. Future research is recommended to add other variables Private Life, Environmental Awareness, Green Mindfulness, Pro-Environmental Identity, and expand the scope of objects so that the results are more representative.